2019
DOI: 10.2298/tsci190412276r
|View full text |Cite
|
Sign up to set email alerts
|

Development of a national index for the purpose of forest fire risk assessments on the example of southern Serbia

Abstract: Original scientific paper https://doi.org/10.2298/TSCI190412276RThe paper presents the results on the study of the possible application of the Canadian Forest Fire Weather Index and the Modified Angstrom Index in forest fire risk assessments. The daily values of these indices for the period 2005-2015 were related to the forest fire database. It was found that there is a relatively weak to moderate correlation between forest fires and the values of the Canadian Forest Fire Weather Index. In order to improve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Studies [10,12] showed that the relationship between forest fires and fire indices existed in different regions of Serbia. In order to improve the wildfire risk assessment, the Angstrom index was modified, and a significant correlation with the forest fires is found in southern Serbia [25]. Beside the fire indices, the raw climate data can be used to estimate fire occurrence.…”
Section: Correlation With Forest Firesmentioning
confidence: 99%
“…Studies [10,12] showed that the relationship between forest fires and fire indices existed in different regions of Serbia. In order to improve the wildfire risk assessment, the Angstrom index was modified, and a significant correlation with the forest fires is found in southern Serbia [25]. Beside the fire indices, the raw climate data can be used to estimate fire occurrence.…”
Section: Correlation With Forest Firesmentioning
confidence: 99%
“…As droughts have been observed to increase in frequency, intensity and duration in Serbia, more frequent wildfires are expected, especially in south-eastern and eastern Serbia. The Modified Angstrom and Nesterov indices can be used to assess the risk of fire, including Serbia (Ratknić et al, 2019;Živanović and Tošić, 2020). Wildfires affect sustainable forest management and incur a substantial loss to forestry.…”
Section: Introductionmentioning
confidence: 99%
“…The FWI system is an important part of the Canadian Forest Fire Danger Rating System (CFFDRS) and was initially developed for conditions of boreal forests in Canada (Wotton, 2009). Later, the FWI system has been adapted to a number of countries with different climates to Canada, such as Indonesia and Malaysia (Groot et al, 2006), or countries of the Mediterranean region, i.e., Spain (Padilla and Vega-García, 2011), Portugal (Carvalho et al, 2008), France (Cloppet and Regimbeau, 2010), Serbia (Ratknić et al, 2019) and Greece (Dimitrakopoulos et al, 2011, Karali et al, 2014. Another fire danger rating system is the National Fire Danger Rating System (NFDRS), which is used in the United States (Deeming et al, 1977).…”
Section: Introductionmentioning
confidence: 99%